2014
DOI: 10.5901/mjss.2014.v5n16p184
|View full text |Cite
|
Sign up to set email alerts
|

Factors Motivating Young South African Women to Become Entrepreneurs

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 22 publications
7
19
0
Order By: Relevance
“…Studies of this phenomenon indicate that women are motivated by some specific factors to enter into business on their own. A literature review of female entrepreneurs suggests that the majority of women are motivated by push factors to start their business and, as such, have low motivation to grow their business (Brush et al , 2006; GEM, 2010; Fatoki, 2014; Rey-Marti et al , 2015). This is attributed to the fact that female entrepreneurs put more emphasis on balancing their families and business, and so they expect less from their business than their male counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies of this phenomenon indicate that women are motivated by some specific factors to enter into business on their own. A literature review of female entrepreneurs suggests that the majority of women are motivated by push factors to start their business and, as such, have low motivation to grow their business (Brush et al , 2006; GEM, 2010; Fatoki, 2014; Rey-Marti et al , 2015). This is attributed to the fact that female entrepreneurs put more emphasis on balancing their families and business, and so they expect less from their business than their male counterparts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In both cases, factor analyses identified four categories of motivational factors among samples of entrepreneurs: extrinsic motives, intrinsic motives, family reasons, and the need for autonomy/independence. Further research (Benzing, Chu and Kara, 2009;Robichaud, Cachon and Haq, 2010;Larsson and Erlandsson, 2010;Zimmerman and Chu, 2013;Fatoki, 2014;Hassan, Ramli and Desa, 2014) found the same groupings as Kuratko et al (1997) and Robichaud et al (2001).…”
Section: Motivations Of Mexican and Moroccan Entrepreneursmentioning
confidence: 62%
“…A 2010 SAMP survey of working-age Zimbabweans in two South African cities (Cape Town and Johannesburg) prior to the amnesty found that 52% held asylum-seeker permits, 19% held work permits and only 2% had acquired permanent residence. 79 Until recently, most migrants from Zimbabwe engaged in circular migration, spending only short periods in South Africa, returning home frequently and showing little inclination to remain in South Africa. The 2010 SAMP survey was limited to migrants who had gone to South Africa for the first time between 2005 and 2010 and painted a very different picture.…”
Section: Contentsmentioning
confidence: 99%